Catch Per Unit Effort (Cpue) Of Purse Seine Fishery For A Period Of 5 Years At The Tumumpa Coastal Fishing Port - Saragih, Mariana; Labaro, Ivor Lembondrong; Pamikiran, Revols D. Ch; Manoppo, Lefrand; Silooy, Fanny (Sam Ratulangi University, 2023)
This study aims to analyze the five-year development of CPUE (catch per unit effort) and to find out the fishing effort of ring seine at PPP Tumumpa and its effect on CPUE periodically. Based on the research results, the CPUE value of large pelagics has decreased every year, where the CPUE value in 2017 was 25.42%, in 2018 it was 25.08%, in 2019 it was 17.71%, in 2020 it was 17.10%. , the last in 2021 was 14.66% and for small pelagics, the CPUE value decreased, where the CPUE value in 2017 was 21.70%, in 2018 it was 17.92%, in 2019 it was 17.19%, in 2018 it was 17.19%. in 2020 is 23.13%, and the last in 2021 is 20.04%. Utilization rates in large and small pelagics are in a state of concern as CPUE decreases yearly.Keywords:Â CPUE, production data, purse seine, utilization rate.AbstrakPenelitian ini bertujuan untuk menganalisis perkembangan lima tahun CPUE (catch per unit effort) dan mengetahui upaya penangkapan perikanan pukat cincin di PPP Tumumpa serta pengaruhnya terhadap CPUE secara periodik. Berdasarkan hasil penelitian nilai CPUE pelagis besar mengalami penurunan setiap tahun, dimana nilai CPUE pada tahun 2017 yaitu 25,42 %, pada tahun 2018 yaitu 25,08 %, pada tahun 2019 yaitu 17,71 %, pada tahun 2020 yaitu 17,10 %, terakhir pada tahun 2021 yaitu 14,66 % dan untuk pelagis kecil nilai CPUE mengalami penurunan, dimana nilai CPUE pada tahun 2017 yaitu 21,70 %, pada tahun 2018 yaitu 17,92 %, pada tahun 2019 yaitu 17,19 %, pada tahun 2020 yaitu 23,13 %, dan terakhir pada tahun 2021 yaitu 20,04 %. Tingkat pemanfaatan pada pelagis besar dan kecil berada dalam keadaan mengkhawatirkan karena CPUE mengalami penurunan setiap tahun.Kata Kunci: CPUE, data produksi, pukat cincin, tingkat pemanfaatan.Â